Teaching of differential and integral calculation basics in Lithuanian schools before the teaching reform in mathematics (in 1918– 1928) - Kastickaitė, Joana; Banionis, Juozas (Lietuvos matematikos rinkinys, 2009)
The article discusses teaching of differential and integral calculation fundamentals before the reform in the teaching of mathematics (1918-1928) with reference to the textbook of Juozas Stoukus “Basics of Infinite Smallness Analysis”, contemporary curricula of higher schools and articles of mathematicians.